Computational Modeling of Quasi-Periodic Rudin-Shapiro Multilayered Band Gap Structure - Bouazzi, Y.; Ben Ali, N.; Alsaif, H.; Boudjemline, A.; Trabelsi, Y.; Torchani, A. (Engineering, Technology & Applied Science Research, 2020)
The optical transmission spectra proprieties of the one-dimensional quasi-periodic multilayered photonic structures according to the Rudin-Shapiro distribution are studied theoretically in this paper by using a theoretical model based on the transfer matrix approach for normal incidence geometry. The influence of the layer number has been studied, i.e. the iteration order of the generating sequence of the quasi-periodic structure on the structure spectral behavior and the width of the Photonic Band Gap (PBG). It was found that the width of the PBG is proportional to the index contrast.